Efeito da ingestão aguda dos chás de gengibre (Zingiber officinale Roscoe) e canela (Cinnamomum sp.) sobre o metabolismo energético, sensação de saciedade e ingestão alimentar de indivíduos saudáveis. - Ana Paula da Costa Soares (2021)
Overweight is a worldwide pandemic that affects more than two billion people. With the advent of social media, alternative weight-loss strategies have become popular but without a proper scientific basis, is the case with "supposedly thermogenic" teas. The aim of this study was to evaluate the acute effect of ginger (Zingiber officinale Roscoe) and cinnamon (Cinnamomum sp.) tea ingestion on energy metabolism, appetitive responses and food intake on healthy individuals. This is an experimental, randomized, open, crossover study, with a minimum interval of seven days between treatments. Three drinks (ginger tea (2g), cinnamon tea (2g) and water (control)) were served accompanied by standardized breakfast. It has 21 volunteers of both sexes (18 to 40 years old, 18.5 to 26kg / m2). Energy expenditure (EG), diet-induced thermogenesis (TID) and respiratory quotient (QR) were measured using indirect calorimetry and urinary nitrogen was analyzed in order to correct nitrogen energy expenditure (GEN), TID and substrate oxidation. Appetizing responses (hunger, satiety, fullness and desire to eat) were assessed using a visual analog scale. The volunteers declared the food record. The ingestion of ginger tea did not alter the EG and TID (p=0,111; p=0,114). However, there as significant increase in GEN in 240 minutes (p=0,002) was observed for the ginger treatment (1420±286kcal) when compared to the control (1324±286kcal), increasing from 95±27kcal (p=0,016) in nitrogenous TID in the ginger tea treatment. The QR values were higher after consumption of ginger tea (0,80±0,05), compared to the control (0,78±0,07) (p=0,038). The oxidation of carbohydrates was also greater in the ginger treatment (-2,9±3,4) compared to the control (-5,3±2,9) (p=0,046). The area under the curve (AUC) of appetite responses did not differ between treatments (p> 0,050). Regarding food intake, there was no difference between treatments regarding energy and macronutrient intake (p> 0,050). For cinnamon tea, there was no change in GE (p=0,582) or GEN (p=0,460), nitrogenous TID (p=0,772) or not (p=0,275), QR (p=0,486) and substrates oxidation (p>0,050). The AUC for hunger (p=0,188) and desire to eat (p=0,104) did not differ between cinnamon tea and water treatment. However, there was a reduction of the satiety feeling (PAUC<0,001) and fullness (PAUC<0,001), comparing to control. The energy consumption of the first meal after treatment was higher in the treatment with cinnamon tea (747±263kcal) compared to the control treatment (609±246kcal), (p = 0.050). There was no difference between treatments regarding the consumption of macronutrients (p> 0.050). For food intake throughout the day after data collection, energy and macronutrient intake did not differ between treatments (p>0,050). We concluded that the acute intake of ginger tea increased the GEN, TID, QR and the oxidation of carbohydrates. Cinnamon tea reduced satiety feeling and fullness and caused greater energy intake in the first meal after treatment.